A systematic literature review on the impact of the COVID-19 pandemic on faculty members’ research performance - Tingsong Li; Xi Yang; Jia Cai (Humanities & Social Sciences Communications)
Abstract The COVID-19 pandemic has profoundly changed faculty members’ lifestyles and work patterns with persisting effects in the post-pandemic era that potentially affect their scientific research. Through a systematic review of 52 articles related to the impact of the COVID-19 pandemic on faculty members’ research performance, this study finds that most of the literature suggests that the pandemic has had a positive impact on academic publications related to COVID-19, but a negative impact on non-COVID-19-related articles. In addition, the negative impact of the pandemic on female faculty members’ scientific research performance is more significant than that of their male counterparts. This study further explores how the COVID-19 pandemic may have affected the academic performance of faculty members. Three internal mechanisms are explored. Firstly, due to the pandemic, faculty members were compelled to adopt a work from home (WFH) model, which has changed their work schedules, led to heightened psychological stress, and required them to adapt to new technologies. Secondly, the pandemic has altered research collaboration patterns. In COVID-19-related fields, the number of research collaborations has gradually increased, with more diverse collaboration teams, though the team size has reduced. Conversely, non-COVID-19-related fields have witnessed a decrease in the overall number of collaborative studies. Thirdly, there have been some adjustments in the allocation of research resources across universities, potentially affecting funding availability for faculty members across various disciplines. Finally, this paper presents future research implications and policy recommendations to support the management and revitalization of university research in the post-pandemic era.